2019
DOI: 10.1364/oe.27.013252
|View full text |Cite
|
Sign up to set email alerts
|

Metasurface generated polarization insensitive Fano resonance for high-performance refractive index sensing

Abstract: A refractive index sensor can provide refractive index measurement and continuously monitor a dynamic process. Plasmonic nanostructure based sensors suffer from severe metal losses in the optical range, leading to the performance degradation. We design and numerically analyze a high-performance refractive index sensor based on the Fano resonance generated by a dielectric metasurface. The figure of merit (FOM) and the maximum quality factor (Q-factor) of the sensor are 721 and 5126, respectively. The maximum mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…As shown in Figure 1a, we propose a metal and dielectric hybrid metasurface. The metal and dielectric are chosen to be Au and TiO 2 , respectively, and the substrate is glass, the permittivity of Au, TiO 2 , and glass reference to the related articles [35,55]. Figure 1b,c show the x-z plane view and x-y plane view of the proposed hybrid metasurface.…”
Section: Structure and Theory Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 1a, we propose a metal and dielectric hybrid metasurface. The metal and dielectric are chosen to be Au and TiO 2 , respectively, and the substrate is glass, the permittivity of Au, TiO 2 , and glass reference to the related articles [35,55]. Figure 1b,c show the x-z plane view and x-y plane view of the proposed hybrid metasurface.…”
Section: Structure and Theory Modelmentioning
confidence: 99%
“…Tang et al investigated sensing applications based on high-Q Fano resonances in graphene coupled systems [52]. Liu et al reported high performance of refractive index sensing in the TiO 2 metasurface generated by the polarization insensitive Fano resonance [55]. Due to the strong optical fields binding characteristics of SPs, the metal and dielectric hybrid metasurface will enhance the sensitivity of the sensor based on Fano resonances.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the presented bilayer grating structure can maintain the function of polarization-selective bidirectional absorption within an incident angle up to 30°. The excited Fano-like resonance mode of the absorber at oblique incidence is conducive to the optical sensing application [ 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…This method provides a new way to measure the phase difference between two orthogonally polarized light, which may bring out more compact polarization measurement devices. Optical sensors based on metamaterials or metasurfaces are widely used in detecting low concentration molecules [285][286][287][288][289][290][291] and small refractive index changes of surrounding mediums [292][293][294][295][296] . Most of these optical sensors are based on the strong resonance and local field enhancement of nanostructures, which can improve the sensitivity of optical responses to the changes of the surroundings.…”
Section: Applications In Wave Field Manipulations Applications In Em mentioning
confidence: 99%